2012
DOI: 10.1002/ajhb.22347
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of 2D:4D finger ratio with androgen receptor CAG and GGN repeat polymorphism

Abstract: In this study, we first found that the left hand 2D:4D ratio was longer than that of the right hand in both males and females. However, we found that both CAG and GGN alleles were not associated with the left hand, right hand, right minus left-hand or mean hand 2D:4D ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
1
19
0
3
Order By: Relevance
“…In accordance with the data in China 18,29, we found that men showed significantly smaller 2D:4D ratios than women in right and left hands. The ROCs analysis showed that the optimal cutoff point of digit ratio for CAD discrimination in male was 0.9505 in both hands with sensitivity 0f 57.8% and specificity of 68% in right hand, and 50.8% and 58.7% in left hand.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the data in China 18,29, we found that men showed significantly smaller 2D:4D ratios than women in right and left hands. The ROCs analysis showed that the optimal cutoff point of digit ratio for CAD discrimination in male was 0.9505 in both hands with sensitivity 0f 57.8% and specificity of 68% in right hand, and 50.8% and 58.7% in left hand.…”
Section: Discussionsupporting
confidence: 91%
“…Genes reported to show an allelic association with 2D : 4D tend to show a failure to replicate. The initial report of an effect of a polymorphism in the androgen receptor gene has not been replicated in larger sample sizes (Hurd et al, 2011;Loehlin et al, 2012;Zhang et al, 2013). A SNP in LIN28B identified in a genome-wide association study by Medland et al (2010) did not replicate with statistical significance in a following study (Lawrance-Owen et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…As females (but not males) have two AR gene copies, either the shorter allele, the longer allele, or the bi-allelic mean can be used. One report (28) reported all three analyses (which led to very similar results), and I used the result for the bi-allelic mean in the present analysis. For two other reports that involved females (29, 30) it remained unclear on which of the three measures their analysis was based.…”
Section: Methodsmentioning
confidence: 87%